Preparasi Pelepah Sawit Dengan Asam Oksalat Dan Pengaruhnya Terhadap Sifat Dan Morfologi Wood Plastic Composite - Andreas Sahat Parsaulian; Bahruddin Bahruddin; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Reduced forest makes the availability of woods as the construction material on the wane. Oil palm frond has a potential to use to decrease utilization of woods directly. The main objective of this study was to evaluate the effect of oxalic acid and thermal pretreatment to morphology and properties of oil palm frond based wood plastic composite (WPC). The temperature of pretreatment were varied at 100oC, 120oC, and 140oC with submersion time 15 minutes. The mass ratio of oil palm frond sized 100 – 200 mesh as filler and polypropylene as a matrix is 30:70. 2% paraffin as plasticizer and 5% maleic anhydride polypropylene as compatibilizer were use as an additive. WPC samples were prepared using internal mixer Labo Plastomill at temperature 180oC and rotor speed 80 rpm. Testing experiments were prepared to mechanical testing consist of tensile and flexural strength and physical testing consist of density, water absorption, and swelling thickness. Scanning Electron Microscopy was used as a morphology testing. The result showed that oxalic acid pretreatment significantly gives an effect to mechanical and physical properties. The best WPC in this study was treated in the 120oC using oxalic acid based on tensile strength with 23.785 MPa, flexural strength 43.2 MPa, density 0.975 gr/cm3, water absorption 1.44%, and swelling thickness 0.17%.Keywords: pretreatment, oil palm frond, wood plastic composite